A IMPORTANCIA DA INOCULAÇÃO DA SEMENTE NA CULTURA DA SOJA (REMUNOM, 2024)
The present work was developed through seed inoculation practices in soybean cultivation, which consists of the introduction of atmospheric nitrogen-fixing bacteria into the soil, which occurs mainly with the genus Bradyrhizobium. These bacteria establish a symbiosis with soybean roots, forming nodules where atmospheric nitrogen is fixed, making it available to the plant. The study was carried out to reduce the need for nitrogen fertilizer, contributing to the environmental and economic sustainability of the work. Furthermore, inoculation improved plant development, increasing the productivity and quality of soybeans. In addition to Bacteria of the Bradyrhizobium genus, there is the practice of co-inoculation, which consists of intercropping with bacteria of the Azospirillum brasiliense genus, which produce phytohormones that stimulate plant development of plants and roots, promoting an increase in the root system and plant development. Therefore, it should be noted that to improve practices, there will also be an analysis of other relevant studies due to the breadth of the topic. To this end, we seek to study the essence of the respective work with an emphasis on biological nitrogen fixation.